On the Manuscript(s) of Lazius’ Description of Transylvania - Csapó, Fanni (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The upsurge of cosmographical and geographical literature can be seen in humanist circles from the 14th century onwards. Beside chorography, the encomium of towns and cities was also a popular genre; some elements of ethnography, natural, economic and political geography were also built into the histography. A century later, this tendency reached Hungary and the social aspiration to presentation of the country appeared in Hungary too. Owing to these factors, chorography of Hungary was written by Miklós Oláh; humanist historians (for instance Antonio Bonfini) also incorporeted geographical digression into their work. Not only descriptions of Hungary, but some geographical descriptions of Transilvania were made in the second half of the 16th century; one of these was written by a 16 th century Viennese humanist polyhistor, Wolfgang Lazius. The purpose of this paper is to provide a description of the three textual variants of the manuscript of the Transylvania-description by Lazius, to explore their relationship to each other, and to establish their order of composition.